Abdominal Compartment Syndrome is an Early, Lethal Complication of Acute Pancreatitis. Issue 6 (June 2013) - Boone, Brian; Zureikat, Amer; Hughes, Steven J.; Moser, A. James; Yadav, Dhiraj; Zeh, Herbert J.; Lee, Kenneth K. W.
Data defining the optimal management of abdominal compartment syndrome resulting from acute pancreatitis are lacking. We investigated the outcomes of patients with acute pancreatitis who underwent surgery for treatment of abdominal compartment syndrome at a tertiary referral center. An electronic database was searched to identify patients with acute pancreatitis who underwent laparotomy between January 1, 2000, and December 31, 2009, for treatment of abdominal compartment syndrome. Twelve patients underwent decompressive laparotomy for abdominal compartment syndrome. The median interval between onset of pancreatitis and laparotomy was 4.5 days. Nine patients underwent a laparotomy within seven days of onset of pancreatitis. As a result of cardiopulmonary instability, four decompressive laparotomies were performed in the intensive care unit. In 11 patients, cardiopulmonary improvement was observed. Statistically significant improvements were seen across multiple physiologic parameters. Despite this initial improvement, six patients (50%) died from multisystem organ failure. Two patients survived without need for pancreatic débridement. Abdominal compartment syndrome is an uncommon but likely underrecognized and highly lethal complication of acute pancreatitis that should be considered in patients who become critically ill early in the course of their pancreatitis. Prompt recognition and decompressive laparotomy may rescue some of these patients and does not mandate future débridement.